(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the essence of the concept of social activism and its gender characteristics, social activism is a comprehensive category, and in the process of education, it means increasing the social activism of students, ensuring that they are active in all areas, knowledge and experience. Opinions about forming skills and increasing initiative are presented.